EVALUATION OF ENERGY EFFICIENCY AND COST BENEFIT FOR THE USE OF METAL ROOF IN SUPERMARKETS THROUGH THE SOFTWARE ENERGYPLUS - Caneppele, Laís Braga; Nogueira, Marta Crista de Jesus Albuquerque; Vasconcellos, Arnulfo Barroso de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707703 This paper aims to analyze the efficiency and cost x benefit the use of three types ofmetal roofing for an supermarket area of 1.907,5 m². It considered the use of aluminum tile,thermal blanket aluminum tile and sandwich tile. The software EnergyPlus was the tool used forthe simulation. The plug-in Openstudio integrated into SketchUp was used for the constructionand editing of the model. It is necessary to insert the physical characteristics of the components,thermal loads internal lighting, general equipment, number of people, maximum internaltemperature of the air to use the air conditioning and climate data from Cuiabá for make the simulation. With the simulation data were evaluated internal temperatures, energy consumptionand demands monthly tariff framework and energy savings for each situation, related to costbenefit.